2010
DOI: 10.1159/000313024
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Bronchopulmonary Dysplasia in Very Preterm Neonates in Europe: Results from the MOSAIC Cohort

Abstract: Background: A considerable local variability in the rate of bronchopulmonary dysplasia (BPD) has been recorded previously. Objectives: The objectives of the present study were to describe regional differences in the rate of BPD in very preterm neonates from a European population-based cohort and to further delineate risk factors. Methods: 4,185 survivors to 36 weeks’ postmenstrual age of 4,984 live-born infants born at 24+0–31+6 weeks’ gestation in 2003 (the MOSAIC cohort) in 10 European regions were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 117 publications
(93 citation statements)
references
References 38 publications
6
81
2
4
Order By: Relevance
“…These were not the expected results and could help explain the contradictory findings in the literature. Indeed, previous studies found a positive association 21,23,33 or no association 10,25,34 between placentamediated complications and BPD. However, a few studies distinguished between preeclamptic women with and without FGR.…”
Section: Discussionmentioning
confidence: 95%
“…These were not the expected results and could help explain the contradictory findings in the literature. Indeed, previous studies found a positive association 21,23,33 or no association 10,25,34 between placentamediated complications and BPD. However, a few studies distinguished between preeclamptic women with and without FGR.…”
Section: Discussionmentioning
confidence: 95%
“…BPD rates ranged from 10.2 to 24.8% for infants between 23-31 wk of gestations in the MOSIAC cohort of 10 European regions (29). The overall incidence of BPD or death was 52%; ranging from 32 to 74% across NICHD Neonatal Research Network centers in infants below 1,250 g (30).…”
Section: Vitamin D Receptor and Bpdmentioning
confidence: 96%
“…Several recent reports have shown that maternal hypertensive disorders of pregnancy are associated with a higher risk for BPD 5,6,14,22 ; however, the underlying mechanism has only recently been clarified in experimental animal studies. Preeclampsia is characterized by maternal endothelial dysfunction that leads to hypertension, proteinuria, and other complications.…”
Section: Figurementioning
confidence: 99%